2008
DOI: 10.1016/j.jfoodeng.2007.03.032
|View full text |Cite
|
Sign up to set email alerts
|

A review of the performance of domestic refrigerators

Abstract: 7This paper reviews the published data on the performance and use of domestic refrigerators 8 throughout the world in the last 30 years. While there is considerable legislation defining 9 maximum temperatures during the production, distribution and retailing of chilled food, as 10 soon as the consumer purchases the food, it is outside of any of these legislative 11 requirements. Inadequate domestic refrigeration or cooling is frequently cited as a possible 12 factor in food poisoning incidents. It is clear fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
2
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 35 publications
6
68
2
5
Order By: Relevance
“…Nunes et al (2009) demonstrated that variations in storage conditions are normally encountered in the cold chain and they have a huge effect on decreasing the quality and shelf life of grapes and other fresh products. However, some authors suggested that the weakest link of the cold chain is the domestic storage, while home refrigerators and freezers frequently present poor temperature control (James et al, 2008;Laguerre et al, 2002). A study performed by Gogou et al (2015) for selected food products in Greece and France supports this argument, revealing that during the domestic storage temperatures may vary from ~ 4 °C to ~ 11 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Nunes et al (2009) demonstrated that variations in storage conditions are normally encountered in the cold chain and they have a huge effect on decreasing the quality and shelf life of grapes and other fresh products. However, some authors suggested that the weakest link of the cold chain is the domestic storage, while home refrigerators and freezers frequently present poor temperature control (James et al, 2008;Laguerre et al, 2002). A study performed by Gogou et al (2015) for selected food products in Greece and France supports this argument, revealing that during the domestic storage temperatures may vary from ~ 4 °C to ~ 11 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat alarming was the notion made by James et al (2008) who reviewed 20 published studies, conducted in parts of Europe, the US, and New Zealand from 1987 to 2006, and found only two studies reporting mean air temperatures of less than 5 °C in domestic refrigerators. Most studies showed a great deal of concordance, citing temperatures in >50% of refrigerators above 5 °C.…”
Section: °C 5 °C Ldt (H) Egr (Log/h) Ldt (H) Egr (Log/h)mentioning
confidence: 99%
“…. using survey data (James, Evans, & James, 2008;Lagendijk, Assere, Derens, & Carpentier, 2008). For example, pasteurized milk, which is supposed to be contaminated with 1 Bacillus cereus spore per gram, can be stored 2 days at 4°C in the factory, 2 days at 7°C at the retail and a few days in the consumer's fridge.…”
Section: Team Work Project: Determination Of the Product Shelf-life Amentioning
confidence: 99%